Merz: Revolusi seni yang membongkar batasan tradisi - Setiyawan, Danu; Sugiarti, Yati (Journal of Culture, Literature and Foreign Language Teaching, 2025)
Merz, pioneered by Kurt Schwitters, advocates for the liberation from the artistic rules that confine it, making it a revolution in the field of art, particularly in German literature. Schwitters depicted this liberation through the representation of traditional and modern visions in his first Merz poem, "An Anna Blume." Therefore, this research aims to elucidate Schwitters' perspective in confronting change and connecting tradition with modernity as depicted in this poem. The approach employed in this research is a semiotic approach utilizing Riffaterre's semiotics theory. The technique used is qualitative descriptive analysis. The primary source of this study is Kurt Schwitters' poem "An Anna Blume." Data collection is conducted through observation, heuristic reading, and hermeneutic reading. The research instrument is the researcher themselves, acting as the human instrument. Data validity is obtained through semantic validity, intrarater, and interrater reliability. Data analysis is carried out using qualitative descriptive analysis. The research findings are as follows: (1) Heuristic reading portrays Anna Blume as breaking old conventions, being mysterious and unique. (2) The discontinuity of expression is caused by meaning replacement meaning deviation, and meaning creation (3) Hermeneutic reading reveals the necessity for tradition and innovation to coexist when facing social and cultural changes. (4) The poem's matrix is the shift in the role of women in the context of modernity, with the model being the coexistence of tradition and innovation. This model is then developed into variants found in each stanza. (5) The potential hypogram in this poem is the integration of tradition and innovation in dealing with change. Meanwhile, the actual hypogram is the November 1918 Revolution and the birth of the Weimar Republic in 1919. Keywords: Analysis, Poetry, Riffaterre, Semiotic, Tradition